1986
DOI: 10.1111/j.1432-1033.1986.tb09681.x
|View full text |Cite
|
Sign up to set email alerts
|

Bohr effect in monomeric insect haemoglobins controlled by O2 off-rate and modulated by haem-rotational disorder

Abstract: The monomeric insect (Chironomus thummi thummi) haemoglobins CTT 111 and CTT IV show an alkaline Bohr effect. The amplitude of the Bohr effect curve of CTT IV is about twice as large as that of CTT 111. In particular, at low pH a time-dependent 'slow' decrease in p s o upon cyclic oxygenation/deoxygenation is observed which is larger if dithionite, instead of ascorbate, is the reducing agent. The decrease of p s o (increase in affinity) correlates with the ratio of haem-rotational components exhibiting an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…This observation is consistent with the invariance of resonance Raman and visible spectra of the CO derivative within the same pH range (9,34,39). Also, in the monomeric globin of the insect Chironomus thummi thummi, the Bohr effect is larger when O 2 rather than CO is the heme ligand (40). These observations support the conclusion that in NGB the heme-bound O 2 , which in globins, including NGB (9), has a Fe(III)O 2 .…”
Section: On the Reaction Of 4-pds With Ngb And Human Hbasupporting
confidence: 79%
“…This observation is consistent with the invariance of resonance Raman and visible spectra of the CO derivative within the same pH range (9,34,39). Also, in the monomeric globin of the insect Chironomus thummi thummi, the Bohr effect is larger when O 2 rather than CO is the heme ligand (40). These observations support the conclusion that in NGB the heme-bound O 2 , which in globins, including NGB (9), has a Fe(III)O 2 .…”
Section: On the Reaction Of 4-pds With Ngb And Human Hbasupporting
confidence: 79%
“…Both globins also have a positively charged amino acid (arginine instead of lysine) at position 67. Remarkably, as in murine Ngb, the heme binds to the globin in two orientations in Chironomus Hb (42,43).…”
Section: Resultsmentioning
confidence: 99%
“…Differences of possible physiological relevance have been reported for two other heme proteins, however. A difference of 27 mV in the reduction potential of the two isomers of cytochrome has been found (Walker et al, 1988), and the Bohr effect of Chironomus thummi thummi hemoglobin has been shown to be different for the two isomers (Gersonde et al, 1986).…”
Section: Heme Isomerismmentioning
confidence: 99%